#TITLE_ALTERNATIVE# - AGUNG CINTER HALIM, ALBERT
Maritime logistics activities in Indonesia can not be separated from the decision to choose shipping routes, ship types, and number of ships. Such decisions affect the cost of maritime logistics that can impact on product price and competitiveness. Kristiana (2016) has developed a simulation model of maritime logistics cost calculations that can be used to choose shipping routes, ship types, and number of ships. Kristiana (2016) compares scenarios in the form of networks, consist of set of shipping routes along with the type and number of ships. In the Kristiana model (2016), the developed algorithm is still specific to certain scenarios and the input model is manual and not user-friendly. In addition, mathematical models can only provide solutions and still require human judgment to be a decision. So in this research, a decision support system that interacts with humans by displaying the input of the model, running the Kristiana simulation model (2016), provide calculations results and proposed decisions with a user-friendly display and accommodate flexible scenarios is designed. The design of decision support systems began with reviewing the system, compiling a decision-making flowchart, and identifying user requirements for system design. Next, conceptualized systems are designed in model management subsystems, data management subsystems, and user-interface subsystems. Reference model used is Kristiana model (2016), while the design of database is done with driven model approach. The operational decision support system design was developed using Microsoft Excel software with Visual Basic for Application feature and MATLAB. The design of decision support systems is tested in terms of algorithms, usage, and requirements fulfillment. The results are the algorithms are appropriate, the usage is not problematic, and the requirements are met. The participants also feel the user-interface was user-friendly. Implementation of decision support system design requires the preparation of human resources with certain conditions as well as training for the use of decision support systems. The use of DSS can shorten decision-making time, eliminate miscalculation, assist decision-making in different circumstances with time and cost savings, and considering human judgement, thus result in better decision.